System dynamics model for remanufacturing system - Afandiyev, Fadai (2015)
Remanufacturing is a process where the used products or cores are restored to look like as good as new products. Remanufactured products have high profitability and sustainability in comparison whit the recycled materials, because it can be retain as value added. The remanufacturing system is more complex that traditional manufacturing. The relationship between the parameters of this system and analyzing their influence on the behavior of the system is more complex, for this “System Dynamics” methodology is used. The aim of this thesis is to improve a system dynamics simulation model for remanufacturing system, by focusing “customer behavior, service agreement whit customer, company reputation and recollection effort” and their influence on the dynamic behavior of the system and analyses these factors effect on the total profit, total cost and collection rate. The objective is to maximize total profit, minimize total cost, and maximize collection rate. For this, 80 different combinations of simulation scenarios are simulated, and the data form this simulation runs is analyzed by using design of experiment approach. Based on these analyses, it can be concluded that all four factors are significant, but company reputation is most significant factor to get the optimized scenario for total profit, cost and collection rate to satisfy the objective of this thesis